[Students working in the Aeronautics Hangar] (1932)
Students working in the Aeronautics Laboratory, circa 1930. Aeronautics department professor Glenn Warren (also known as H. G. Warren, first professor in Aeronautics) standing with students in suit and tie. The wing of Cal Poly?s second plane that students built, known as ?Miss Poly? or CP-1, is visible in the upper foreground. This plane was built in 1929. This photo was printed in the 1933 El Rodeo Yearbook.